Geleneksel İrfan Diliyle Alevi Bektaşi Metinlerin Anlatılma İmkanı (Journal of Alevism-Bektashism Studies, 2012)
This article drew attention to fact that most of the topics which appear in the classical texts have to be evaluated in the frame of the gnostic tradition of the Alevis and Bektashis (irfan). Thus it was argued, that the geography and the message of Alevism and Bektashism, must be understood by referring to the tradition Gnostic writings of the Alevis and Bektashis. For a better understand the article was rendered with examples of the Vilayetname (hagiography) of Hacı Bektaş.